Adherence and Attrition in a Web-Based Lifestyle Intervention for People with Metabolic Syndrome. - Leila Jahangiry; Davoud Shojaeizadeh; Ali Montazeri; Mahdi Najafi; Kazem Mohammad; Mehdi Yaseri (Tehran University of Medical Sciences, 2014)
The aim of this study was to determine adherence and attrition rates in a lifestyle intervention for people with metabolic syndrome.Adherence and attrition data from a randomized controlled trial were collected. Participants were classified as adherence group if they completed assessments at 3 and 6 months follow-up and as attrition group if they did not. Physical activity and quality of life was measured using the International Physical Activity Questionnaire (IPAQ) and the Short Form Health Survey (SF-36). Generalized Estimating Equations (GEE) was used to explore predictors of attrition.The mean age of participants (n=160) was 44.1 years. Attrition rate in the intervention and control groups at first follow-up were the same (20%). However, the control group had significantly higher attrition rate (%33.7) compared to the intervention group (%20) at 6 months follow up. Results showed that low educated participants were more likely to not stay in the study than better educated participants (OR=2.95,CI:1.39-6.33,P=0.05). According with length of the study, attrition was decreased at six month (OR=0.66,CI:0.52-0.83,P